Relationship Between Serum Testosterone Levels and Kidney Stones Prevalence in Men - Huang, Fang; Li, Yongchao; Cui, Yu; Zhu, Zewu; Chen, Jinbo; Zeng, Feng; Li, Yang; Chen, Zhiyong; Chen, Hequn (Frontiers in Endocrinology, 2022)
Abstract Background: The role of serum testosterone levels in male renal stone formation remains controversial. This study aimed to evaluate the relationship between serum testosterone levels and kidney stones prevalence in males. Methods: We conducted a cross-sectional study based on the data from the National Health and Nutrition Examination Survey 2011-2016, which included 6633 male participants, to investigate the association between testosterone levels and the prevalence of kidney stones. Results: In this study, using the highest quartile of serum testosterone as a reference, a logistic regression model adjusted for confounders in all participants showed that the first quartile (OR 1.375, p=0.016), the second quartile (OR 1.348, p=0.021), and the third quartile (OR 1.472, p=0.003) of testosterone significantly increased kidney stones risks. In the 41-60 age group, the ORs of kidney stones risk in the first, second, and third of serum testosterone were 1.904 (P =0.005), 1.599 (P =0.040), and 1.734 (P =0.015) respectively. This trend can also be found in the 61-80 years group, except the first quartile of serum testosterone (OR:1.169, P =0.436). Adjusted smoothed curves suggest a non-linear relationship between the 8 quantiles of serum testosterone and the risk of kidney stones in all participants and the 61-80 age group and a significant negative relationship in the 41-60 age group (OR:0.921, P =0.0193). But no correlation was been seen in the 20-40 group. Conclusions: Serum testosterone levels were significantly inversely associated with the prevalence of kidney stones in men over 40 years of age, but no correlation was been seen in the 20-40 group. The role of testosterone in stone formation should be redefined and its effect should be further verified.